Era uma vez no Oeste: considerações sobre as relações de poder na Câmara de Tratamento de Conflitos Agrários e Fundiários do Oeste do Pará. - SACRAMENTO, Thiago Guimarães do (Universidade Federal do Oeste do Pará, 2022)
The Chamber for the Treatment of Agrarian and Land Conflicts in the Persecutor's Office of Pará (CTCAF) has become an integral part of the self-composition systemof conflicts in Pará and has the proposal to draw up works with hard cases related to agrarian, landandsocio-environmental issues. This research was carried out in order to answer to what extent the CTCAF installation process in Santarém allows us to understand the relations of powerbetween the social actors who participated in it. This study was carried out using participant observation and extensive analysis of records made in the formof an ethnography of documents, as well as the peacebuilding theoretical framework. The research is justifiedbythe importance of observing the impacts of self-composition practices in agreement andconflict of interests in the Amazon region. Studying about the installation process presentsastratum of the performance of these practices and was an alternative in viewof the suspensionof CTCAF activities due to the advent of the Covid 19 pandemic. Sociopolitical territory by human groups present and conflicts over the use of land and natural resources have showna range of overlapping interests. By analyzing the power relations between the various actorspresent in this space, their clash of interests and defense and argumentation strategies aroundthese own interests, it was possible to observe the training and multiplication strategiesofleaders in grassroots communities as the main strategy of the Chamber until now. Andyethow the actors at the regional level, in particular the Persecutor's Office of the Stateof Pará,in the figure of the Agrarian Justice Prosecutor, and the Federal University of WesternPará(UFOPA), in the figure of the Amazon Restorative Justice Clinic (CJUÁ), playedstrategicroles in ensuring a plurality of voices in the installation of the CTCAF.